If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 7 = 7x + 13 Reorder the terms: 7 + 2x = 7x + 13 Reorder the terms: 7 + 2x = 13 + 7x Solving 7 + 2x = 13 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 7 + 2x + -7x = 13 + 7x + -7x Combine like terms: 2x + -7x = -5x 7 + -5x = 13 + 7x + -7x Combine like terms: 7x + -7x = 0 7 + -5x = 13 + 0 7 + -5x = 13 Add '-7' to each side of the equation. 7 + -7 + -5x = 13 + -7 Combine like terms: 7 + -7 = 0 0 + -5x = 13 + -7 -5x = 13 + -7 Combine like terms: 13 + -7 = 6 -5x = 6 Divide each side by '-5'. x = -1.2 Simplifying x = -1.2
| .11x+x=163 | | 1r^2-3r-70=0 | | m^2-4m-96=0 | | -3(8a-9)=5(9-5a) | | 3x+6x-8x= | | u^2=15u | | 2(3x+3)=5(x-5) | | 1/4(20+x)=30 | | 2(x-0.5)=4(x+4) | | p^2=10p+11 | | 1v^3=49v | | x(x+18)=-80 | | x-5=sqrt(-7x+43) | | y^2+10y=4x+3 | | 1d^2+29d+100=0 | | 5+0.5=2.67y+6 | | (2w+3)w=54*54 | | -4(5n-5)=2n | | x^2-17x=18 | | 2x/5+2/3(3x/5)+18=x | | 7(3n)/2=-6 | | -9x-1=-3 | | p(t)=1.8(1.4) | | Rl+rl=E | | 2+2w=8 | | 2w+3w=54 | | (22-13x)4=x-7 | | 7(2)-5=9 | | 5(x+3)-2=-12 | | 2(45+56y)=78 | | (2w-3)w=54 | | 4+25x=14 |